Acute isotonic hyponatremia after single dose histidine-tryptophan-ketoglutarate cardioplegia: an observational study. (July 2021) - van Houte, Joris; Bindels, Alexander J; Houterman, Saskia; Dong, Phi Vu; den Ouden, Monique; de Bock, Nina E; Verberkmoes, Niels J; Curvers, Joyce; Bouwman, Arthur R
Introduction: Histidine-tryptophan-ketoglutarate cardioplegia is used for prolonged myocardial protection in complex cardiac surgery. Administration leads to acute hyponatremia in a majority of patients, because of its low sodium concentration (15 mmol/L). However, histidine-tryptophan-ketoglutarate solution's osmolality is slightly hypertonic (310 mOsm/kg). Hypothesized was that acute isotonic hyponatremia will be induced, which does not need to be corrected with hypertonic saline. Methods: Cardiac surgery patients who received histidine-tryptophan-ketoglutarate cardioplegia were included in this prospective single center study. Serial blood samples were taken from each patient at five different time points: after induction of anesthesia (T1) and 10 minutes (T2), 6 hours (T3), 12 hours (T4), and 18 hours (T5) after administration of histidine-tryptophan-ketoglutarate cardioplegia, respectively. Blood samples were analyzed for sodium concentration, osmolality, and acid-base balance. Results: Twenty-five patients were included. Median blood sodium levels decreased from 140 [138-141] at T1 to 128 [125-130] mmol/L at T2 (p < 0.001). At T3, T4, and T5, median blood sodium concentrations were 136 [134-138], 139 [137-140], and 140 [137-142] mmol/L, respectively. Median osmolality was 289 [286-293] at T1 and increased to 296 [291-299] mOsm/kg (p < 0.001) at T2. At T3, T4, and T5, osmolality was 298 [292-302], 298 [294-304], and 300 [297-306] mOsm/kg, respectively. Median pH decreased from 7.38 [7.36-7.40] at T1 to 7.30 [7.27-7.32] at T2 (p < 0.001). Conclusion: Administration of histidine-tryptophan-ketoglutarate cardioplegia during cardiac surgery leads to acute moderate to severe isotonic hyponatremia, which resolves spontaneously in the first 18 hours perioperatively. Correction with hypertonic saline is not necessary.